Les usages du numérique actuels dans le supérieur en Suisse et en Belgique - Aurélien Fiévez; Natasha Noben (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This research involves studying the digital uses of 221 Swiss and Belgian university teachers. The aim is to understand the uses actually implemented in higher education in these two countries. In order to categorise these uses, a typology of digital uses in education has been constructed. It aims to include both the uses made by teachers to prepare their lessons and teach and the uses they request from their students. This typology was established on the basis of existing literature (Denis, 2001; Paquette, 2002; Bégin, 2008; Peraya, 2008; Vuorikari et al., 2022) and includes both face-to-face and remote, synchronous and asynchronous uses. The aim of this research is therefore also to check the applicability of this typology and to adapt it on the basis of feedback from teachers.